The armament of polish mercenary infantry in the first part of the 16th century - Aleksander Bołdyrew (Fasciculi Archaeologiae Historicae)
The armament of Polish mercenary infantry in the first part of the 16th century was discussed on the basis of preserved source materials, mostly manuscripts. Much attention was paid to the users of the weapon, their territorial and social origin, and the role of military formations of foot soldiers in the battles discussed both, from the point of view of tactics and strategy. Numerous armatures were used at that time, for instance spear, pavise, rifles and badges. At least three changes in armament were observed which resulted from the conditions of the battlefield. The trial to give direction to further research of this issue was made